Manajemen Event Olahraga dalam Penyelenggaraan Jakarta Football Expo 2024 - Utomo, Bambang Setyo; Fairuzzabadi, Fairuzzabadi; Luthfi, Mohammad (Universitas Prof. Dr. Moestopo (Beragama), 2025)
This study aims to analyze the event management process applied by the committee in organizing the Jakarta Football Expo 2024 tournament using a qualitative descriptive method. Data were collected through in-depth interviews and documentation. The findings show that the committee has implemented event management systematically across five stages: research, design, planning, coordination, and evaluation. In the research stage, the committee analyzed soccer community needs and reviewed previous competition systems. The design stage developed the theme 'Jakarta Kota Bola, Kami Rindu Juara' to promote youth talent development. Planning involved organizing the event structure and task division. Coordination was carried out through online and offline platforms to engage all stakeholders. Evaluation assessed audience participation, match management, finance, and promotion. The study concludes that the Jakarta Football Expo 2024 applied event management effectively, but improvements are needed in promotion, sponsorship, and legal endorsement. This research contributes to the study of sports event management in Indonesia and offers practical insights for organizers.